An investigation of original equipment manufacturer's optimal remanufacturing mode and engagement strategy. (10th December 2020) - Zhou, Qin; Yuen, Kum Fai
Abstract: This study considers an original equipment manufacturer (OEM) who (a) relies on a contract manufacturer (CM) to produce its new products, and (b) engages the CM again or an independent remanufacturer (IR) to perform the remanufacturing operations of branded patented products through either authorization or outsourcing. This study chiefly investigates the optimal remanufacturing engagement strategy (i.e., engage a CM or an IR) and remanufacturing mode (i.e., authorization and outsourcing) that should be taken by an OEM. This paper derives the optimal responses of the three parties (i.e., OEM, CM, and IR) by comparing the outcomes of different remanufacturing engagement strategies and remanufacturing modes under two settings, depending on whether the wholesale price is exogenously or endogenously given. The results suggest that the OEM is better off adopting the authorization remanufacturing mode by either working with the CM or the IR when the wholesale price is exogenously given. When the wholesale price is endogenously determined by the CM, the best strategy for the OEM is to work with the IR using the outsourcing approach. The CM and the IR also show different preferences between the two modes. The IR or CM that engages in remanufacturing always prefers the outsourcing mode than the authorization mode in the two settings. However, when the CM does not engage in remanufacturing, it is better off adopting the authorization mode when the wholesale price is exogenously given or when the remanufacturing cost is relatively low in the endogenized wholesale price setting.